Impacts of edaphic factors on communities of ammonia-oxidizing archaea, ammonia-oxidizing bacteria and nitrification in tropical soils. - Vidya de Gannes; Gaius Eudoxie; William J Hickey (PLoS ONE, 2014)
Nitrification is a key process in soil nitrogen (N) dynamics, but relatively little is known about it in tropical soils. In this study, we examined soils from Trinidad to determine the edaphic drivers affecting nitrification levels and community structure of ammonia-oxidizing bacteria (AOB) and ammonia-oxidizing archaea (AOA) in non-managed soils. The soils were naturally vegetated, ranged in texture from sands to clays and spanned pH 4 to 8. The AOA were detected by qPCR in all soils (ca. 10(5) to 10(6) copies archaeal amoA g(-1) soil), but AOB levels were low and bacterial amoA was infrequently detected. AOA abundance showed a significant negative correlation (p<0.001) with levels of soil organic carbon, clay and ammonium, but was not correlated to pH. Structures of AOA and AOB communities, as determined by amoA terminal restriction fragment (TRF) analysis, differed significantly between soils (p<0.001). Variation in AOA TRF profiles was best explained by ammonium-N and either Kjeldahl N or total N (p<0.001) while variation in AOB TRF profiles was best explained by phosphorus, bulk density and iron (p<0.01). In clone libraries, phylotypes of archaeal amoA (predominantly Nitrososphaera) and bacterial amoA (predominanatly Nitrosospira) differed between soils, but variation was not correlated with pH. Nitrification potential was positively correlated with clay content and pH (p<0.001), but not to AOA or AOB abundance or community structure. Collectively, the study showed that AOA and AOB communities were affected by differing sets of edaphic factors, notably that soil N characteristics were significant for AOA, but not AOB, and that pH was not a major driver for either community. Thus, the effect of pH on nitrification appeared to mainly reflect impacts on AOA or AOB activity, rather than selection for AOA or AOB phylotypes differing in nitrifying capacity.